Peer evaluation system - Tai, Jiann Tsong (2022)

(untitled)
This project is the development of a peer evaluation system web app for academic purposes and to resolve the student’s problems that occurred during the assignment or research group forming. This project will be used to solve the problem of research or assignment groups that face a high risk of getting messy with not cooperating or low attitude and performance team member, and this system as the community for students or researchers to form their group. The methodology to manage this development process is an agile methodology to maximize the flexibility of the project and shorten the development life cycle. This project will be developed as a web-based system and the architecture will be using is MVC (Model-View-Controller) architecture pattern with using of Laravel MVC framework in PHP written language. This project aimed to provide a references source to the public when they decide to form their group, they can refer to the evaluation rating and record available in the system before they accept to join, this system will allow the evaluation aspect collect from the community’s users and let the suggested idea with a majority of the vote to be added to the evaluation form for fair evaluation purpose. This system also allows for group forming for research or assignment groups, and search or sort for the evaluation rating rank for them to check their peer’s evaluation rating. In the development process, the MySQL database will be used for the system to manage and store the system’s data. The tools involved to develop the system are the Argon Design System CSS framework to build the layout and the Object-Oriented Programming of PHP. To verify the usability of the system, it will be tested with the black box testing when it has finished development.